Kajian Pelaksanaan E-Government pada Pemerintahan Desa Citalem Kecamatan Cipongkor Kabupaten Bandung Barat - Agus Diana, Bambang; Sunarya, Amud; Harta, Ridho (Jayapangus Press, 2024)
The development of e-Government has been a government commitment, as outlined in Presidential Instruction Number 3 of 2003 regarding the Policy and National Strategy for e-Government Development. However, the implementation of this policy has not been entirely smooth at the local government level, causing obstacles to e-Government as a primary tool of governance. One factor hindering the development of e-Government is resistance to change. Law Number 6 of 2014 concerning Villages states that governance at the village level can be modernized through the implementation of Information Technology via Village e-Government. Nevertheless, in-depth research on the application of e-Government in Village Governance is required. The aim of this research is to examine the implementation of e-Government in Citalem Village, Cipongkor District, West Bandung Regency. The research is qualitative with a descriptive approach, utilizing both primary and secondary data obtained through surveys, observations, and literature reviews. The informants were selected using purposive sampling. The research revealed a four-stage model based on the complexity of technology and organization, as well as the level of data and information integration. The planned development of this model involves McFarlan’s Analyst Grid to provide a detailed explanation of strategic modules, high potential areas, supporting elements, and key operational aspects. E-Government in Citalem Village faces challenges due to human resource limitations. Village leaders need to coordinate with the Regency government, provide IT training, and foster motivation to enhance public services through e-Government, aiming for good governance.